A Surface Science Approach to Designing and Understanding Single-Atom Alloy Catalysts at the Atomic-Scale - Hannagan, Ryan. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Chemistry.; Advisor: Charles Sykes.; Committee: Arthur Utz, Mary Shultz, and Mark Hersam.; Keywords: Physical chemistry, Chemical engineering, and Computational chemistry.